Neurological diseases in the context of the COVID-19 pandemic (review of the literature) - O. V. Rodionova; V. А. Sorokoumov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Currently, there is a world-wide pandemic of a new viral infection — COVID-19. The Russian Federation ranks third in the world in the number of detected cases. In the context of the current pandemic, neurological departments are reassigned to infectious diseases departments, the routing of patients is changing, and patients with neurological symptoms are less likely to seek medical help because of the fear of SARS-CoV-2 infection. At the same time, early diagnosis of neurological diseases, including acute cerebrovascular accident, becomes even more complicated, and treatment standards are not always fully applicable. This situation further emphasizes the medical and social significance of neurological diseases. There is evidence that acute cardiovascular diseases can develop as a complication of SARS-CoV-2 infection and vice versa — preexisting cardiovascular diseases aggravate the course of COVID-19. The direct and indirect effects of the virus on the central and peripheral nervous system are discussed. Cases of necrotizing encephalopathy, Guillain-Barr syndrome, a clinical picture of skeletal muscle lesions associated with the COVID-19 infection are described. This article provides an overview of the available world literature on this topic.